Investigation of the Effects of Depression on Substance Abuse in Sports Science Faculty Students - Çolak, Hülya; Ünal, Hakan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
This research was conducted to examine the effects of depression states on substance abuse tendency and compare it according to various variables of students studying at Gazi University Faculty of Sport Sciences. The research group consisted of 422 students, 220 of whom were females, and 202 of whom were males. In the research, the Item Use Tendency Scale and Beck Depression Scale were used as the data collection tools. The data obtained in the study were analyzed using SPSS for Windows 22.0 program. In the analysis of the research variables, parametric methods were used because the number of samples (n = 422) was high enough according to the law of large numbers. Number, percentage, average, and standard deviation were used as descriptive statistical methods in the evaluation of the data. The t-test was used to compare continuous quantitative data between two independent groups, and the Oneway Anova test was used to compare continuous quantitative data between more than two independent groups. Scheffe test was used as the second-degree analysis to determine the differences after the Anova test. Pearson Correlation and regression analysis were used among the continuous variables of the study. As a result, it was determined that depression increased the tendency of substance use among students of the participants. The tendency to use substances was higher among female students than male students, and the tendency to use substances was not affected by age, marital status, department, average income, and class status.